Experimental investigation on the influence of tunnel crossing blast vibration on upper gas pipeline - Jiang, Nan; Jia, Yongsheng; Yao, Yingkang; Sun, Jinshan; Zhu, Bin; Wu, Tingyao (Engineering failure analysis, 2021)
[Display omitted] •Field explosion tests of the full-scale buried pipeline were carried out.•Safety control standard of peak particle velocity (PPV) of pipeline was proposed.•Dynamic response of pipeline with different buried depth were discussed.•Evaluation of pipeline considering buried depth and blasting vibration was studied. In order to effectively control the damage of blasting construction to the upper pipeline, it is necessary to reveal the impact of blasting vibration on the pipeline. By conducting an on-site crossing blast experiment under the pre-buried full-scale gas pipeline, the vibration distribution characteristics of pipeline and ground surface soil in the process of blast crossing the upper gas pipeline were analyzed based on field blasting vibration monitoring and dynamic strain test. Combined with the results of dynamic strain analysis of pipeline in field test, the safety control standard of peak particle velocity (PPV) of the pipeline was proposed based on the allowable strain criterion of the pipeline. Moreover, a 3D numerical model was established to analyze the response characteristics of upper buried gas pipeline subjected to blasting vibration and its reliability was verified using the field monitoring data. Considering the influence of pipeline burial depth, the numerical calculation experiments were carried out, and the dynamic response characteristics of pipelines subject to blasting vibration under different buried depth conditions in urban areas were discussed. At last, the functional relationships between the PPV of pipeline and the PPV of ground surface soil above the pipeline, the peak effective stress (PES) of the pipeline and the PPV of ground surface soil were established, and the safety control and evaluation of the pipeline considering the buried depth under the influence of blasting vibration could be realized.